An AHP-GIS Based Approach for Site Suitability Analysis of Solar-Wind Projects in Santa Marta, Colombia - Olivero-OrtÃz, VÃctor; Robles-AlgarÃn, Carlos; Viloria-Porto, Julie (International Journal of Energy Economics and Policy, 2021)
This paper presents an analysis to determine the suitable areas for the implementation of solar-wind projects in Santa Marta, Colombia. For this, an approach that integrates the decision-making tool of the Analytical Hierarchical Process (AHP) with Geographic Information Systems (GIS) was used. To identify the selection criteria, the existing literature and the renewable resources available in the study area were considered. Seven sub-criteria were identified (solar irradiation, wind speed, protected areas, armed conflict, indigenous reservations, populated zones and roads), which were weighted with the AHP by 15 experts with experience in projects with renewable energies. After performing a consistency analysis, it was found that 5 experts were consistent, while another 5 were discarded for being highly inconsistent. A consistency correction method was implemented for the remaining 5 experts, in order to have 10 experts for the weighting process. Each sub-criterion represents a map of the study area, which were superimposed in a GIS environment to implement the weighting obtained with the experts. A global map for the implementation of renewable energy projects, considering environmental, social and local infrastructure criteria was obtained. The map was classified into five categories: not suitable, marginally suitable, moderately suitable, highly suitable and optimally areas. Keywords: Renewable Energy, Analytical Hierarchical Process, Energy Planning, Geographic Information Systems JEL Classifications: Q20, D70, Q42, D81 DOI: https://doi.org/10.32479/ijeep.11266